Ecosystem Restoration and Conservation in Singkarak Lake Protection Area: Impacts of Reclamation - Adam, Tommy; Muhammad, Hanif; Randa, Ilham Gusri (SEAMEO BIOTROP, 2026)
Reclamation and landfilling activities within protected zones pose serious threats to ecosystem sustainability by altering natural land–water interactions and violating the essential functions of Singkarak Lake’s riparian buffer. This study aims to map the extent of reclamation, examine legal violations related to spatial and environmental permits, and assess ecological and economic losses. A mixed-methods approach was used, including geospatial analysis, normative legal review, and ecocentric valuation of environmental damage. Results show that 2,976 m² of land was illegally reclaimed within the protected lake boundary. Overlay with the regional spatial plan confirms non-compliance with zoning regulations and the absence of required permits. The total estimated loss amounts to Rp 3,383,291,152, largely driven by disrupted hydrological functions and reduced land utility.